Fine-scale spatial genetic structure in the frankincense tree Boswellia papyrifera (Del.) Hochst. and implications for conservation - Addisalem, A.; Duminil, J.; Wouters, D.; Bongers, F.; Smulders, M. (Springer, 2016)
The fine-scale genetic structure and how it varies between generations depends on the spatial scale of gene dispersal and other fundamental aspects of species’ biology, such as the mating system. Such knowledge is crucial for the design of genetic conservation strategies. This is particularly relevant for species that are increasingly fragmented such as Boswellia papyrifera. This species occurs in dry tropical forests from Ethiopia, Eritrea and Sudan and is an important source of frankincense, a highly valued aromatic resin obtained from the bark of the tree. This study assessed the genetic diversity and fine-scale spatial genetic structure (FSGS) of two cohorts (adults and seedlings) from two populations (Guba-Arenja and Kurmuk) in Western Ethiopia and inferred intra-population gene dispersal in the species, using microsatellite markers. The expected heterozygosity (HE) was 0.664–0.724. The spatial analyses based on kinship coefficient (Fij) revealed a significant positive genetic correlation up to a distance of 130 m. Spatial genetic structure was relatively weak (Sp = 0.002–0.014) indicating that gene dispersal is extensive within the populations. Based on the FSGS patterns found, we estimate indirectly gene dispersal distances of 103 and 124 m for the two populations studied. The high heterozygosity, the low fixation index and the low Sp values found in this study are consistent with outcrossing as the (predominant) mating system in B. papyrifera. We suggest that seed collection for ex situ conservation and reforestation programmes of B. papyrifera should use trees separated by distances of at least 100 m but preferably 150 m to limit genetic relatedness among seeds from different trees.